Complete rehabilitation of compromised full dentitions with adhesively bonded all-ceramic single-tooth restorations: Long-term outcome in patients with and without amelogenesis imperfecta. (March 2018) - Klink, Andrea; Groten, Martin; Huettig, Fabian
Abstract: Objectives: This clinical follow-up evaluated the long-term outcome of full-mouth rehabilitations with adhesively bonded all-ceramic restorations in patients suffering from amelogenesis imperfecta (AI) or affected by extensive tooth wear including a loss of the vertical dimension of occlusion. Materials and methods: Included for evaluation were all patients treated with adhesively bonded monolithic single-tooth restorations made of silicate or lithium disilicate ceramics; allowing a maximum four missing teeth and a facial feldspathic veneering of LDS anterior crowns. After treatment, patients have been enrolled in a recall program for dental check-ups including quality assessment of the restorations. Patients answered the oral health impact profile (OHIP-14) at their last visit. Results: Seventeen patients (mean age = 35 ± 18 years) were observed up to 16.5 years (mean: 6.2 ± 3.8 years). 12 out of 450 restorations failed due to core fracture (n = 7), tooth fracture (n = 2), one secondary caries, one chip-off grade 3, and one fixed dental prosthesis due to discomfort. The overall mean survival rate of the single-tooth restorations was estimated 99.4% at 5 and 91.4% at 10 years. The overall mean success rate was estimated 92.6% at 5 and 81.4% at 10 years, mainly due to chip-offs and crack formation (27 out of 31 relative failures). The mean annual failure rates (AFR) range between 1.5 and 2% over the years, but non-AI patients were affected more frequently by early technical complications in the facial veneering of anteriors, resulting in an AFR ranging between 5.2 and 4%. Quality assessment revealed stable color, form and marginal integrity in all patients up to ten years. The distribution of OHIP values is comparable to the representative sample of healthy patients. Conclusion: Adhesively bonded single-tooth restorations provided a high clinical quality in the long-run. However, while the survival and success were excellent in AI patients, restorations in non-AI patients were affected by a higher complication rate, likely related to a higher risk profile due to a history of bruxism and tooth wear.